Waste Material of Propolis as a Film Forming Agent Intended to Modify the Metronidazole Release: Preparation and Characterization - de Alcantara Sica de Toledo, Lucas; Rosseto, Hélen Cássia; Ravani, Laura; Cortesi, Rita; Luciano Bruschi, Marcos (Current Drug Delivery, 2016)
Metronidazole is an antimicrobial agent utilized for the treatment of protozoa and anaerobic bacteria infections. Many times, it is necessary to modify the metronidazole release, and the development of modified release systems may be suggested. In this study, we are able to investigate the use of the residue normally thrown out from the preparation of propolis extracts (BP) as strategy to modify the metronidazole release. We prepared films containing polymeric adjuvant (gelatin or ethylcellulose) and metronidazole, by solvent casting method. Density, mechanical properties, water vapor permeability (WVP), moisture uptake capacity (MUC), thermogravimetry, differential scanning calorimetry, Fourier transform infrared spectroscopy (FT-IR), and in vitro metronidazole release were investigated. Thickness and density of the preparations indicated that the compounds were homogeneously dispersed throughout. Mechanical properties were influenced by film composition. Films containing gelatin showed higher resistance to stress while those containing ethylcellulose presented greater flexibility. The greater the adjuvant concentrations lower the resistance to rupture and the elasticity, but higher MUC and WVP of formulations. FT-IR tests suggested interactions between BP and the adjuvants. Films were capable to protect the metronidazole and changed its release profile. BP films are of great practical importance constituting a novel strategy to modify the metronidazole release.
Keywords: gelatin